Analysis of Raw Material Inventory Control in Tofu Business in Wonomarto Village - Putri Purwaningrum; Agus Purnomo (International Journal of Economics, Business and Innovation Research, 2024)
Tofu Business in Wonomarto Village, North Lampung Regency, is one of the local business entities operating in the food industry. Raw material inventory control involves a number of key aspects, including the determination of optimal ordering quantities, safety stock management, and supply risk management. Inventory control methods and models, such as EOQ as well as JIT, can provide valuable insights in determining the optimal ordering quantity and managing inventory more efficiently. However, the implementation of these methods needs to be adapted to the specific conditions and needs of Tofu Business as well as the characteristics of the local food industry. By conducting a careful analysis of raw material inventory control, Tofu Business can identify opportunities to improve operational efficiency, reduce costs, as well as improve customer service. This will help the company to remain competitive in a dynamic market and support long-term business growth in Wonomarto Village, North Lampung Regency.